Understanding coupling in the context of an SOA comparative architecture. - Linthicum, David
Since the beginning of computing we've been dealing with the notion of coupling, or the degree to which one component is dependent on another component in both the domain of an application or an architecture. Lately, the movement has been towards loose coupling for some very good reasons, but I'm not sure that many architects out there building SOAs understand the motives behind this.